The distribution of minimum air temperature in Lithuania - Jokimaitis, Arvydas; Petronaitis, Darius (Lietuvos matematikos rinkinys, 2019)
The article authors detected distribution estimates of minimum air temperature in Lithuania. Also estimated ultimate minimum temperature record.